Emas Logam Mulia Bersertifikasi LBMA sebagai Instrumen Ketahanan Finansial Calon Jamaah Haji: Kajian Literatur atas Hedging Inflasi, Kesesuaian Syariah, dan Keamann Regulasi Bappebti - Ade Wiwi; Haekal Rizqi Hannie; Avionita Nuraini (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study reviews the role of LBMA-certified physical gold bullion (LM Antam), tradable in physical and digital forms, as a financial resilience instrument for Indonesian Hajj pilgrims. As of May 2026, Indonesia's Hajj waiting list reached 5.63 million pilgrims with an average waiting period of 26 years, while the 2026 Hajj Organizing Cost (BPIH) was IDR 87.40 million per pilgrim. Official historical data (1995–2026) show that gold prices achieved a compound annual growth rate (CAGR) of 16.4%, substantially exceeding the growth of Hajj costs (6.0%) and inflation (4.5%). Consequently, the gold required to finance the BPIH declined from 298 grams in 1995 to only 31 grams in 2026, an 89.6% reduction. This narrative literature review synthesizes published secondary data using descriptive analysis and the Hedging Effectiveness Ratio (HER), complemented by a juridical-normative analysis of Sharia compliance and Indonesia's regulatory framework. The findings indicate that gold achieved an HER of 2.47 against BPIH growth, outperforming Sharia Hajj savings (0.50), Sharia deposits (0.67), and Sharia mutual funds (1.33). Official BPKH data further show that gold prices explain 45.4% of BPIH variation, supporting previous empirical evidence. Moreover, LBMA-standard digital gold traded on Bappebti-licensed platforms complies with DSN-MUI fatwas and is protected under the Bullion Bank regulatory framework. This study proposes a Hajj Financial Resilience Framework (HFRF) that positions LBMA gold bullion as a Sharia-compliant and sustainable strategy for strengthening Hajj financial planning and achieving istitha'ah maliyyah.